Pengaruh Model PBL Terhadap Keaktifan Siswa dan Hasil Belajar Kimia SMA/MA pada Materi Koloid - Muhammad Husny Roza; Marini Damanik (Universitas Negeri Medan, 2022)
This study aims to determine whether there is a significant difference in student learning activities that are taught using the Problem Based Learning (PBL) model compared to the conventional model on colloidal material. The samples of this study were two students of class XI IPA MAN 2 Medan Silent Model, 1 (one) experimental class using the PBL model, 1 (one) control class using the conventional learning model. The research instrument used was an observation sheet on student learning activities and a total test instrument with 20 questions. The results showed that student learning activities in the experimental class were 89.33 and in the control class was 85.86, while student learning outcomes in the experimental class were 91.33 and in the control class was 86.88. In testing the data through the SPSS 22.0 for Windows program, if Sig. (2-tailed) < 0.05, then Ha is accepted. Meanwhile, if Sig. (2-tailed) > 0.05, then Ha is rejected. From the test results obtained results for hypothesis 1, where the value of Sig. obtained is smaller than 0.05, namely 0.01, so it can be concluded that the first hypothesis is accepted. From the test results for the results of hypothesis 2, where the value of Sig. obtained is smaller than 0.05, namely 0.02, so it can be concluded that the second hypothesis is accepted. For the hypothesis 3, where rcount = 0.64 while rtable at = 0.05 (N=36) is 0.36. Because rcount > rtable, then Ho is rejected, which means Ha is accepted.Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan yang signifikan aktivitas belajar siswa yang dibelajarkan dengan model Problem Based Learning (PBL) dibandingkan dengan model konvensional pada materi koloid. Sampel penelitian ini adalah dua siswa kelas XI IPA MAN 2 Model Medan diam1 (satu) kelas eksperimen menggunakan model PBL, 1 (satu) kelas kontrol menggunakan model pembelajaran konvensional. Instrumen penelitian yang digunakan lembar observasi aktivitas belajar siswa dan instrumen tes jumlah dengan 20 soal. Hasil penelitian menunjukkan aktivitas belajar siswa pada kelas eksperimen sebesar 89,33 dan pada kelas kontrol sebesar 85,86, sedangkan hasil belajar siswa pada kelas eksperimen sebesar 91,33 dan pada kelas kontrol sebesar 86,88. Dalam pengujian data melalui program SPSS 22.0 for Windows, jika Sig. (2-tailed) < 0,05, maka Ha diterima. Sedangkan jika Sig. (2-tailed) > 0,05, maka Ha ditolak. Dari hasil pengujian didapatkan hasil untuk hipotesis 1, dimana nilai Sig. diperoleh lebih kecil dari 0,05 yaitu 0,01, sehingga dapat disimpulkan hipotesis pertama diterima. Dari hasil pengujian untuk hasil hipotesis 2, dimana nilai Sig. diperoleh lebih kecil dari 0,05 yaitu 0,02, sehingga dapat disimpulkan hipotesis kedua diterima. Untuk hipotesis 3, dimana rhitung = 0,64 sedangkan rtabel pada = 0,05 (N=36) adalah 0,36. Karena rhitung > rtabel, maka Ho ditolak yang berarti Ha diterima.